Partitioning the variation of woody plant β‐diversity in a landscape of secondary tropical dry forests across spatial scales. (2nd July 2012) - López‐Martínez, J.O.; Hernández‐Stefanoni, J.L.; Dupuy, J.M.; Meave, J.A.
Abstract: Question: What is the relative importance of forest successional age, environmental heterogeneity, landscape structure and spatial structure of sampling sites on β‐diversity of tropical dry forests (TDF)? How do the magnitude of β‐diversity and the relative influence of factors, processes and mechanisms driving β‐diversity differ at different spatial grains? What are the effects of stand age on β‐diversity? Location: Yucatán Peninsula, México. Methods: Floristic composition was obtained from a hierarchical survey performed in 276 sites distributed across 23 sampling landscapes (SL) (12 sites per SL). Land‐cover classes were derived from the classification of multi‐spectral SPOT 5 satellite imagery. We calculated landscape metrics of patch type for each SL, and characterized local soil conditions for each sampling site. A principal coordinates of neighbour matrices (PCNM) analysis was performed to estimate spatial variables, and partial redundancy analysis was used to decompose variation into spatial, stand age and landscape structure components. Results: The magnitude of β‐diversity varied with spatial scale (grain size), and was larger at the local than at the landscape grain. The magnitude of β‐diversity also decreased slightly but significantly with successional age. There were significant differences in species composition among vegetation classes. Environmental factors (local soil conditions, as well as landscape structure) and spatial structure both contributed to woody plant β‐diversity in our TDF landscape, but their relative importance was scale‐dependent. At the local grain size, both the environment (mainly soil conditions) and the spatial structure strongly affected β‐diversity, while at the landscape grain, environmental factors (variation in soil conditions, as well as landscape configuration) played a more prominent role. Conclusions: The magnitude of β‐diversity decreased with increasing spatial grain and successional age, while the relative importance of mechanisms influencing β‐diversity was scale‐dependent: both niche partitioning and dispersal limitation affect β‐diversity at the local grain size, while niche partitioning prevails at the landscape grain. Abstract : We investigated the relative importance of successional age, environmental heterogeneity, landscape structure and spatial structure on β‐diversity of tropical dry forests at different spatial scales. The magnitude of β‐diversity decreased with increasing spatial grain and successional age. Both the environment and the spatial structure influenced β‐diversity at the local grain size, environmental factors were more important at the landscape grain.